Impact of climate change on berthing areas in ports of the Balearic Islands: adaptation measures - Sierra, Joan Pau; Sánchez-Arcilla, Agustín; Gironella, Xavier; Gracia, Vicente; Altomare, Corrado; Mösso, César; González-Marco, Daniel; Gómez, Jesús; Barceló, Mateo; Barahona, Cristina (Frontiers in Marine Science, 2023)
Climate change generates impacts on coastal areas due to sea-level rise and potential modifications in wave and storm surge patterns. Since harbours are located in littoral areas, they will experience different impacts associated to such processes. In this paper, the effects of climate change on port berthing areas in terms of operability are quantified. The study is focused on the ports of the Balearic Islands (Western Mediterranean Sea) and analyses the loss of operability due to the reduction of freeboard in berthing structures and the potential variation in agitation within these harbours during the 21st century, considering two different climate scenarios (RCP4.5 and RCP8.5) and two-time horizons (2045 and 2100). In addition, adaptation measures to address such impacts are proposed and their cost estimated. The results indicate that climate change will not generate significant changes in wave agitation due to negligible variations in wave patterns under future scenarios. On the contrary, sea-level rise will cause huge increases of inoperability for berthing structures due to insufficient freeboard: 10.5% under RCP4.5 or 20.5% under RCP8.5 in 2045, increasing to 57.1% (RCP4.5) and even 83.2% (RCP8.5) in 2100.